(untitled) - Phye, Gary D. (San Diego, 1997)
A handbook drawing heavily on a developmental, constructivist approach to teaching methods from elementary school through high school in the subject areas of reading, writing, math, science, and critical thinking. The 33 contributing education scholars emphasize the implementation of theory and research by identifying specific teaching techniques related to the construction of knowledge, motivation strategies, assessment of reasoning, reading diagnosis, current practices in teaching composition and math, and the incorporation of critical thinking into the elementary school curriculum.
Keywords: Learning, Psychology of,Constructivism (Education),Thought and thinking,Tâm lý giáo dục học,Tư duy và suy nghĩ; Study and teaching